Effect of Helicobacter pylori on gastrointestinal microbiota: a population-based study in Linqu, a high-risk area of gastric cancer. Issue 9 (19th December 2019) - Guo, Yang; Zhang, Yang; Gerhard, Markus; Gao, Juan-Juan; Mejias-Luque, Raquel; Zhang, Lian; Vieth, Michael; Ma, Jun-Ling; Bajbouj, Monther; Suchanek, Stepan; Liu, Wei-Dong; Ulm, Kurt; et al.
Abstract : Objective: Gastrointestinal microbiota may be involved in Helicobacter pylori- associated gastric cancer development. The aim of this study was to explore the possible microbial mechanisms in gastric carcinogenesis and potential dysbiosis arising from H. pylori infection. Design: Deep sequencing of the microbial 16S ribosomal RNA gene was used to investigate alterations in paired gastric biopsies and stool samples in 58 subjects with successful and 57 subjects with failed anti- H. pylori treatment, relative to 49 H. pylori negative subjects. Results: In H. pylori positive subjects, richness and Shannon indexes increased significantly (both p<0.001) after successful eradication and showed no difference to those of negative subjects (p=0.493 for richness and p=0.420 for Shannon index). Differential taxa analysis identified 18 significantly altered gastric genera after eradication. The combination of these genera into a Microbial Dysbiosis Index revealed that the dysbiotic microbiota in H. pylori positive mucosa was associated with advanced gastric lesions (chronic atrophic gastritis and intestinal metaplasia/dysplasia) and could be reversed by eradication. Strong coexcluding interactions between Helicobacter and Fusobacterium, Neisseria, Prevotella, Veillonella, Rothia were found only in advanced gastric lesion patients, and were absent in normal/superficial gastritis group. Changes in faecal microbiota included increased Bifidobacterium after successful H. pylori eradication and more upregulated drug-resistant functional orthologs after failed treatment. Conclusion: H. pylori infection contributes significantly to gastric microbial dysbiosis that may be involved in carcinogenesis. Successful H. pylori eradication potentially restores gastric microbiota to a similar status as found in uninfected individuals, and shows beneficial effects on gut microbiota.